Causal relationships between metabolic syndrome, plasma metabolites, and female reproductive diseases: insights from a two-step mendelian randomization approach - Li Li; Juanjuan Ma; Ningyu Sun; Panwei Hu; Yi Lin; Qinhua Zhang (Nutrition & Metabolism)
Abstract Background Female reproductive diseases—including endometriosis (EMs), uterine fibroids (UFs), polycystic ovary syndrome (PCOS), gestational diabetes mellitus (GDM), eclampsia, ectopic pregnancy (EP), infertility, miscarriage, and ovarian aging—pose significant global health challenges. Metabolic syndrome (MetS) is characterized by a series of metabolic irregularities and has been linked to distinct plasma metabolomic profiles. Investigating the etiological connections among MetS, plasma metabolites, and female reproductive diseases is essential for devising effective prevention and treatment strategies. Objective This study sought to evaluate the causal relationships among MetS, plasma metabolites, and female reproductive diseases using a two-step Mendelian randomization (MR) methodology. Methods Initially, MR investigations were conducted to determine the causative impact of MetS on nine female reproductive diseases utilizing genome-wide association study (GWAS) data procured from European-descent populations. Statistically significant associations were identified for five diseases: UF, PCOS, GDM, eclampsia, and miscarriage. One hypothesis is that plasma metabolites may contribute to these associations. Subsequently, comprehensive MR analyses were performed using GWAS data on 233 plasma metabolites to examine causal relationships between these MetS-associated reproductive conditions and eight distinct classes of plasma metabolites. Sensitivity analyses, replication studies, and colocalization assessments were performed to validate the reliability of the outcomes. Results MetS was identified as a causal factor for increased risks of UF, PCOS, GDM, eclampsia, and miscarriage. Further MR analyses revealed that specific plasma metabolites might causally affect the risk of female reproductive diseases: Eclampsia: Protective associations were observed with lipid molecules in large and very large high-density lipoprotein (HDL) particles, including cholesterol esters and total cholesterol. Conversely, triglycerides in large HDL particles and indicators related to small HDL particles were linked to increased risk. PCOS: Risk factors included elevated levels of triglycerides in HDL particles, various very low-density lipoprotein metabolites, acetone, 3-hydroxybutyrate, and conjugated linoleic acid. GDM: Increased glucose levels were associated with increased GDM risk. Conclusions This investigation established that MetS causally elevates the risk of certain female reproductive diseases and identified plasma metabolites that influence these conditions. These findings enhance the understanding of the etiological pathways involved in MetS and reproductive disorders, highlighting plasma metabolites as potential biomarkers or therapeutic targets.